Understanding Health Disparities in Preeclampsia: A Literature Review - Conklin, Mary B.; Wells, Brittney M.; Doe, Emily M.; Strother, Athena M.; Tarasiewicz, Megan E. Burnett; Via, Emily R.; Conrad, Lesley B.; Farias-Eisner, Robin (American Journal of Perinatology, 2023)
Preeclampsia is a multifactorial pathology with negative outcomes in affected patients in both the peripartum and postpartum period. Black patients in the United States, when compared to their White and Hispanic counterparts, have higher rates of preeclampsia. This article aims to review the current literature to investigate how race, social determinants of health, and genetic profiles influence the prevalence and outcomes of patients with preeclampsia. Published studies utilized in this review were identified through PubMed using authors' topic knowledge and a focused search through a Medline search strategy. These articles were thoroughly reviewed to explore the contributing biosocial factors, genes/biomarkers, as well as negative outcomes associated with disparate rates of preeclampsia. Increased rates of contributing comorbidities, including hypertension and obesity, which are largely associated with low access to care in Black patient populations lead to disparate rates of preeclampsia in this population. Limited research shows an association between increased rate of preeclampsia in Black patients and specific APOL1, HLA-G, and PP13 gene polymorphisms as well as factor V Leiden mutations. Further research is required to understand the use of certain biomarkers in predicting preeclampsia within racial populations. Understanding contributing biosocial factors and identifying genes that may predispose high-risk populations may help to address the disparate rates of preeclampsia in Black patients as described in this review. Further research is required to understand if serum, placental, or urine biomarkers may be used to predict individuals at risk of developing preeclampsia in pregnancy.Key Points
Keywords: preeclampsia; hypertensive disorders of pregnancy; maternal morbidity and mortality; health disparities